Bhamaha’s Kavyalamkara: A Critical Study of Poetry, Poetics and their Ancillary Issues - Jagruti B Bheda (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2021)
Finding out the criterion of good poetry and nature of aesthetic delight leads one to think questions such as: What is poetry? What constitutes its body? What is definition of poetry? What is its purpose and what is the nature of delight it imparts to the sympathetic reader? What constitutes the difference between ordinary conversational speech and scientific speech? What are the essential qualities that a poet should possess? Sanskrit literary criticism bears witness to endeavours to arrive at a satisfactory solution to these problems where in Bharata's Natyashashtra is the first available critique on aural-visual arts and aesthetic pleasure related to it. He also gives the requisites of Kavya, ten gunas, ten doshas and four alamkaras. But his treatment of poetry is considered as a factor auxiliary to drama.